Akibat Hukum Terhadap Tidak Dilakukan Penghapusan (Roya) Jaminan Fidusia Setelah Kredit Lunas - Ni Putu Sawitri Nandari; Dewa Krisna Prasada; Kadek Julia Mahadewi; Tania Novelin; Dewa Ayu Putri Sukadana (Jurnal Hukum Sasana, 2023)
Legal obligation is an action that must be done by someone. Every action taken is a form of a sense of responsibility for the problems that are happening, be it legally or morally. Therefore, obligations will always be attached to human life in carrying out social activities. Rules regarding the obligation for fiduciary recipients to carry out fiduciary write-offs (roya) if the agreed debt has been paid off, but it is also necessary to know about the legal consequences if the obligation to write-off (roya) fiduciary guarantees is not carried out, it can result in losses for the fiduciary giver. In this case the problem arises "What are the legal consequences for not carrying out the elimination of (roya) fiduciary guarantees after the credit is paid off. The research method used is a juridical-normative type of research that places law as a system of norms in studying and analyzing the legal consequences of not eliminating (roya) fiduciary guarantees. The type of approach used is the statutory regulation approach and the legal concept analysis approach. The results of the discussion review related to the legal consequences of not carrying out the elimination (roya) of fiduciary guarantees found no strict rules regarding this matter, both in Law no. 42 of 1999, PP no. 21 of 2015, Permenkumham No. 9 of 2013, and Permenkumham No. 10 of 2013, because the things that are regulated are still limited to the obligation to remove (roya) fiduciary guarantees, so there is no threat of punishment or legal sanctions for violators. Meanwhile, legal remedies that can be taken by fiduciary providers who suffer losses due to the actions of fiduciary recipients who are negligent in carrying out the fiduciary guarantee elimination (roya) are by filing a lawsuit against the law (PMH).